1992
DOI: 10.1002/jbmr.5650070509
|View full text |Cite
|
Sign up to set email alerts
|

Specific binding of parathyroid hormone to living osteoclasts

Abstract: We show that osteoclasts bind parathyroid hormone (PTH) in a manner that displays the properties of receptor-dependent hormone binding, that is, saturability, time dependence, temperature dependence, and hormone specificity. Osteoclasts were isolated from the endosteum of 2 to 3 week chick tibiae and maintained in culture for 4-6 days. Bovine PTH-(1-84) was biotinylated with N-hydroxysuccinimidobiotin. Biotinyl-PTH (btPTH, 10(-5)-10(-11) M) was added to the cultured osteoclasts for 2-20 minutes. After rinsing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The classical action is based on the initial understanding that the major biological activities of PTH are subserved by the 34‐residues in its N‐terminal domain and that the PTH residues located beyond position 34 are largely irrelevant 79–81 . Non‐classical actions are now known to require additional regions of the peptide hormone and include binding of intact PTH to rat and avian osteoclasts; 82–85 the actions unique to intact PTH are reviewed elsewhere 86 …”
Section: Endocrine Regulation Of Ca2+ Transportmentioning
confidence: 99%
“…The classical action is based on the initial understanding that the major biological activities of PTH are subserved by the 34‐residues in its N‐terminal domain and that the PTH residues located beyond position 34 are largely irrelevant 79–81 . Non‐classical actions are now known to require additional regions of the peptide hormone and include binding of intact PTH to rat and avian osteoclasts; 82–85 the actions unique to intact PTH are reviewed elsewhere 86 …”
Section: Endocrine Regulation Of Ca2+ Transportmentioning
confidence: 99%
“…It is not surprising that a kinetically distinct response is observed compared to PTH for which the osteoclast expresses a membrane receptor. 15,16 The magnitude of the stimulation by pertussis toxin was found to be smaller than that produced by PTH which may be a result of the relative number of NADPH oxidase molecules which are activated, however, the accurate quantification of the initial flux, j 0 , is difficult because it is very sensitive to the rate of disproportionation of superoxide during the transit between the cell and the detector electrode (Fig. 3).…”
Section: Simulation Of Superoxide Generation By Osteoclasts-character...mentioning
confidence: 99%
“…In view of the significant role of O 2 À in osteoclastic bone resorption, it is important to understand the precise intracellular signaling that is involved in the regulation of free radical production. Although it was originally believed that the modulation of osteoclast activity by major hormones, such as parathyroid hormone (PTH), 1,25-dihydroxycholecalciferol D 3 , and oestrogens is mediated indirectly via cells of osteoblast lineage, several reports have shown that osteoclasts possess receptors for PTH, 15,16 1,25-dihydroxycholecalciferol D 3 17 and oestrogens. 18 Indeed, the exposure of individual avian osteoclasts to PTH has been observed to stimulate hydrogen ion production via a G-protein coupled receptor.…”
Section: Introductionmentioning
confidence: 99%